PENGARUH CASH TURNOVER, RECEIVABLE TURNOVER, DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET PADA PERUSAHAAN SUBSEKTOR KAYU DAN PENGOLAHANNYA YANG TERDAFTAR DI BEI PERIODE 2017 2023 - Azrinindita, Meisya Nabila; Nurhamdi, Muhamad (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to analyze the effect of Cash Turnover, Receivable Turnover and Total Asset Turnover on Return on Assets in wood and processing subsector companies listed on the Indonesia Stock Exchange for the period 2017-2023. This study uses an associative quantitative approach with secondary data obtained from the Company's financial statements. The sample of this study uses a saturated sample, namely by using all populations consisting of four companies. Data processing in this study was carried out using Eviews-12 software. Data analysis in this study includes descriptive statistical tests, classical assumption tests, panel data regression tests, hypothesis tests and determination coefficient tests, the selection of regression models was carried out using the Chow test and the Hausman test, based on these tests the estimation model used in this study is the fixed effect model (FEM). The test results show that partially cash turnover does not have a significant effect on ROA with a calculated T value of 0.400767 < Ttable 2.06390 with a prob value of 0.6926> 0.05, receivable turnover does not have a significant effect on ROA with a calculated T value of 0.726682 < Ttable 2.06390 with a prob value of 0.4754> 0.05, total asset turnover does not have a significant effect on ROA with a calculated T value of 1.404768 < Ttable 2.06390 with a prob value of 0.1747> 0.05. Simultaneously, the three independent variables have a significant positive effect on ROA with a calculated F value of 3.098292> Ftable 3.01 with a prob value of 0.024714 <0.05. with a contribution of 31.80% while the remaining 68.2% is influenced by other factors outside this research.